Physical Activity in Neurological Disorders: A Narrative Review - Turgut, Busra Aktaş; Naz, İlknur (European Journal of Therapeutics, 2023)
Physical activity levels of people with chronic neurological disorders are lower than those of healthy people. Problems in neurological disorders, including gait abnormalities, muscle weakness/loss of strength, spasticity, tremor, fatigue, balance disorder, and incontinence, results in lower physical activity level. After determining the situations that are contraindicated for physical activity, the patients should be evaluated by physiotherapists, and possible risks that may occur should be determined. Many studies have demonstrated that physical activity significantly reduces mortality and morbidity, increases community participation, and improves health-related quality of life. These benefits show that increased physical activity and exercise should be part of the standard management of neurological disorders. In these patients, physical activity programs should be structured individually by providing appropriate environmental conditions and safety, following the assessment of the functional status and severity of the disease. The duration, intensity, and type of planned physical activity should be adjusted individually; Appropriate rest intervals should be given during the activity, and termination criteria should be determined according to individual tolerance. This literature review aims to provide an up-to-date overview of physical activity recommendations for individuals with chronic neurological disorders.